The effect of cerium ions on the structure, porosity and electrochemical properties of Si/Zr-based hybrid Sol-Gel coatings deposited on aluminum - Rodic, Peter (2018)
This study was focused on the synthesis and characterization of Si/Zr-based hybrid sol-gel coatings with and without the addition of cerium(III) ions. The coatings were deposited on aluminum aiming to act as an effective and ecologically harmless alternative to toxic chromate coatings. The chemical composition, structure, thermal properties and porosity of the non-doped and Ce-doped coatings containing various Zr contents were examined by Raman spectroscopy and photothermal beam deflection spectroscopy. The corrosion properties of the coated aluminum substrates were studied using AC and DC electrochemical methods in 0.1 M NaCl electrolyte solution. Barrier and protecting properties of the coatings were monitored upon long-term immersion in chloride solution using electrochemical impedance spectroscopy. The effect of cerium ions was two-fold: on the formation of a more condensed Si−O−Zr network structure and on the formation of Ce-based deposits, which diminish the rate of cathodic reaction at the coating/metal interface. These effects acted synergistically and resulted in the creation of the coatings with effective barrier and active corrosion protection.